Modelling The Effect of Infrastructure Development Acceleration on Sustainable Economic Growth in Indonesia - Mubin, Chairul (CSID Journal of Infrastructure Development, 2019)
Infrastructure development promotes economic growth. The government of Indonesia accelerates infrastructure development to increase its competitiveness. Lack of funding for infrastructure development in Indonesian State Budget causes the government to seek other sources of funding, primarily debt.  The object of this research is infrastructure investment and economic growth in Indonesia. The objective of this research is to develop a model for analysing the effect of debt financing in infrastructure development, and then develop the proposed financing scheme to reduce the negative effects. This study is the first to use engineering economy and portfolio management approach for projecting economic growth. The results show that higher investment in infrastructure development generates higher economic growth and private participation in infrastructure investment can reduce outstanding debt. Additionally, the importance of the project’s economic rates of return must be considered in infrastructure investment decision making.